Evaluation of the surgical treatment outcomes for abnormal uterine bleeding in menopausal women - Tran, Doan Tu; Nguyen, Phu Hao; Hoang, Ngoc Tu; Le, Si Phuc An; Chau, Khac Tu (Tạp chí Y Dược Huế, 2024)
Background: Menopause is determined after 12 consecutive months of amenorrhoea in women with regular menstruation. During this period, women often encounter many health disorders that affect quality of life such as vascular disorders, insomnia, migraines, breast pain, menstrual disorders, and urogenital symptoms,…This study aims to survey the causes of abnormal uterine bleeding in postmenopausal women undergoing surgery and the surgical treatment outcomes in menopausal women. Materials and method: A cross-sectional descriptive study was constructed in 32 women of menopausal age hospitalized for abnormal uterine bleeding at the Center of Obstetrics and Gynecology, Hue Central Hospital, from December 2022 to December 2023. The questionnaire is designed to collect general information, menstrual history, reason for hospitalization, etc. Clinical examination to evaluate abnormal uterine bleeding. Uterus and adnexal ultrasound, sonohysterography (if possible) to evaluate the reason and to evaluate endometrial thickness. Treatment methods include curettage of the uterine cavity to obtain specimens for pathology to rule out malignant originations or/and surgery to eliminate the cause. For endometrial cancer, cancer staging according to FIGO (Federation Internationale de Gynecologie et d’Obstetrique). Results: The mean age and standard deviation of the patients was 56.2 ± 7.8 years. Endometrial hyperplasia and uterine polyps were the main causes with 56.3% and 21.9%, respectively. The major treatment method was uterine curettage and biopsy accounted for 46.8%, following with hysteroscopy and hysterectomy (open/laparoscopic) with 37.5% and 15.7%, respectively. 96.9% of cases had no complications after treatment, the only complication obtained in the study was bleeding, accounting for 3.1%. Conclusion: Endometrial hyperplasia is one of the main causes of abnormal uterine bleeding in menopausal women. Uterine curettage/biopsy and hysteroscopy are safe and reliable methods for evaluating and treating these lesions. The surgical treatment results are relatively safe and only mild complications occur